Chemical composition and activity of a biofilm during the start-up of an airlift reactor - Lopes, F. A. (1999)
For the successful operation of a biofilm reactor, it is important to characterise the fixed biomass, its activity and composition. The purpose of this research is to monitor the biofilm characteristics of an airlift reactor, namely its composition in terms of exopolymers (polysaccharides and proteins), attached biomass, thickness, total proteins, as well as its activity in terms of substrate consumption rates. During the early phases of biofilm development, a high exopolymer production was observed, which helped in promoting the initial cell adhesion. The high turbulence with strong abrasion conditions might also trigger the excretion of those polymers. Low levels of extracellular proteins were detected, showing that the total proteins in the biofilm were mainly intracellular. The biofilm accumulation on the carrier was accompanied by an increase in biological activity; however, at the end of the experiment, the substrate consumption rates (surface reaction rate and specific removal rates) decreased, probably due to a reduction in the cellular density within the biofilm.